AJARAN KETUHANAN DALAM LONTAR BUBUKSAH - ecy wulandari12 (Jnanasiddhanta : Jurnal Teologi Hindu, 2022)
One of the religious texts whose text contains divine teachings is Lontar Bubuksah which specifically explains about Shiva Buddha. Bubuksah is an imaginative story script about a religious literary work, as a story with a religious breath expressing the ideals and essence of liberation of the soul towards a pure nature, namely Moksa, in the Bubuksah text it tends to be Guruistic which takes its source from the doctrine of Shiva (Bhatara Guru) as a god. highest. Gagakaking represents Shiva's doctrine while Bubuksah represents Buddhist doctrine. which Bubuksah as a representation of the Buddhist pedanda in Bali which comes from the teachings of Bhatara Guru (Guruistick sources). In the end Gagakaking and Bubuksah represented the revered priest Sewa Sogata as a manifestation of Bhatara Guru. This is what distinguishes it from other Buddhist teachingsKeywords: Divinity, Bubuksah